Synthesis, characterization, and antibacterial activities of SnO and SnO@FeCl2 nanoparticles using Olea europaea subsp. Africana (Mill.) P.S. Green mediated green - Numan Khan; Sajjad Ali Shah; Muhammad Hubab; Sidra Tul Muntaha; Ibrar Khan; Azam Hayat; Mujaddad Ur Rehman; Tawaf Ali Shah; Jaouad Bensalah; Abdel-Rhman Z. Gaafar; Musaab Dauelbait; Mohammed Bourhia (CyTA - Journal of Food)
In the present study, tin oxide nanoparticles SnONPs and iron doped with tin oxide SnO@FeCl2-NPs were synthesized using extracts of Olea europaea subsp. Africana (Mill.) P.S. The bio-synthesized nanoparticles showed tremendous antibacterial and photocatalytic activities using the agar well diffusion method for antibacterial activity. Our results showed high activity of both NPs against the crystal violet dye and urinary tract caused by Bacteria. The NPs, in particular, SnO@FeCl2-NPs showed significant photocatalytic activity against crystal violet, which was very high as compared to SnONPs. In the case of SnO, the data showed that after the first 20 min of exposure, only 9.8% degradation was observed while after 160 min 79.9% degradation was observed. By using SnO@FeCl2–NP catalyst, the data shows that in initial 20 min the degradation recorded was 10% with the increase in exposure time, and the percentage of degradation reached 86.1%.